The Effect of Inquiry Learning Model Based on Cooperative Script on the Student Learning Achievement - Eni Ermawati; Suratno Suratno; Pujiastuti Pujiastuti (Pancaran Pendidikan, 2019)
Biology is a science that has fundamental dimensions. Biology studies about living things. One of the things learned in Biology is the concept of Animalia. Inquiry learning model based on the cooperative script. The research referred to quasi-experimental research by applying inquiry learning model based on Cooperative Script in X MIPA 5 class as an experimental class and STAD learning model in X MIPA 1 class as a control class conducted at SMAN 1 Arjasa, Jember in the even semester of 2018/2019 academic year. The inquiry learning model based on cooperative script aimed to improve students' learning achievement. The result of data were analyzed  by using covariance analysis (ANAKOVA) which showed that the inquiry learning model based on cooperative script had a significant effect of p = 0,000 with the results of 49.95 in the control class and 54.12 in the experimental class on students' cognitive of grade X at SMAN 1 Arjasa, Jember. The test results of the independent sample t-test implemented in the invertebrate concept had a significant difference to psychomotor students at p = 0,000 with the results of 80.40 in the experimental class and 67.67 in the control class which revealed that from the results obtained both included in the good category.